Oral cancer screening practices of oral health professionals in Australia - Rodrigo Mariño (BMC Oral Health, 2017)
Abstract Background To evaluate oral cancer-related screening practices of Oral Health Professionals (OHPs - dentists, dental hygienists, dental therapists, and oral health therapists) practising in Victoria, Australia. Methods A 36-item survey was distributed to 3343 OHPs. Items included socio-demographic and work-related characteristics; self-assessed knowledge of oral cancer; perceived level of confidence in discussing oral health behaviors with patients; oral cancer screening practices; and self-evaluated need for additional training on screening procedures for oral cancer. Results A total of 380 OHPs responded this survey, achieving an overall response rate of 9.4%. Forty-five were excluded from further analysis. Of these 335 OHP, 72% were dentists; (n = 241); either GDP or Dental Specialists; 13.7% (n = 46) were dental hygienists; 12.2% (n = 41) were oral health therapists, and the remaining 2.1% (n = 7) were dental therapists. While the majority (95.2%) agreed that oral cancer screening should be routinely performed, in actual practice around half (51.4%) screened all their patients. Another 12.8% “Very rarely” conducted screening examinations. The probability of routinely conducting an oral cancer screening was explored utilising Logistic Regression Analysis. Four variables remained statistically significant (p < 0.0001). Results indicate that the likelihood of conducting an oral cancer screening rose with increasing levels of OHPs’ confidence in oral cancer-related knowledge (OR = 1.35; 95% CI: 1.09–1.67) and with higher levels of confidence in discussing oral hygiene practices with patients (OR = 1.25; 95% CI: 1.03–1.52). Results also showed that dental specialists were less likely to perform oral cancer screening examinations compared with other OHPs (OR = 0.18; 95% CI: 0.07–0.52) and the likelihood of performing an oral cancer screening decreased when the “patient complained of a problem” (OR = 0.21; 95% CI: 0.10–0.44). Conclusion Only half the study sample performed oral cancer screening examinations for all of their patients. This study provides evidence of the need for further oral cancer-related education and screening training for OHPs, which is vital to enhance oral cancer prevention and early detection.